Enzyme butilcholinesterase activity variation in hormonal contraception users - Vásquez, Llermén (2000)
OBJECTIVE: To evaluate enzyme butilcholinesterase activity in women using two hormonal contraceptives, norgestrel ethinylestradiol and medroxyprogesterone acetate, using alkaline phosphatase as indirect liver marker. MATERIAL AND METHODS: Women attending family planning program at El Agustino "7 de Octubre" health center, continuing users of hormonal contraception for over six months. Fasting blood was obtained and enzymatic activity was measured in serum. RESULTS: Users of both contraceptives had significant increase in butilcholinesterase activity compared with control group; medroxyprogesterone users had 30% more elevated values; 12% of norgestrel ethinylestradiol and 18% of medroxyprogesterone users had values beyond +/- 2SD. Alkaline phosphatase activity increased a significant 8% only in medroxyprogesterone users. CONCLUSIONS: Medroxyprogesterone acetate caused more and longer butilcholinesterase activity variation than oral norgestrel ethinylestradiol.